Forced conversion in Christianity, Judaism and Islam : coercion and faith in premodern Iberia and beyond - García-Arenal, Mercedes,; Glazer-Eytan, Yonatan, (Handbook of Oriental Studies. Section 1 The Near and Middle East;, 2020)
Focusing on the Iberian Peninsula but examining related European and Mediterranean contexts as well, Forced Conversion in Christianity, Judaism and Islam traces how Christians, Jews, and Muslims grappled with the contradictory phenomenon of faith brought about by constraint and compulsion. Forced conversion brought into sharp relief the tensions among the accepted notion of faith as a voluntary act, the desire to maintain "pure" communities, and the universal truth claims of radical monotheism. Offering a comparative view of an important yet insufficiently studied phenomenon in the history of religions, this collection of essays explores the ways in which religion and violence reshaped these three religions and the ways we understand them today.